“TEACHER, YOUR VOICE……” EXPLORING STUDENTS PERCEPTIONS ON THE USE OF AUDIO FEEDBACK - Flora Debora Floris` (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The purpose of this study was to examine students' perceptions of audio feedback for assignments in their writing class. Data were collected through interviews. The findings highlight the fact that the students would like to see more of this type of feedback across their courses. The findings also indicate that providing feedback to students via audio files is feasible despite some pitfalls of this format. Guidance for teachers concerning the effective use of audio feedback and suggestions for further research are presented at the end of the paper.